Criminalizing dissent: A critical examination of anti-terror laws, preventive detention and the erosion of due process in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The relationship between national security and civil liberties remains one of the most contested issues in constitutional democracies. In India, anti-terror legislation and preventive detention laws have increasingly been criticized for their potential misuse against political dissent, activists, journalists, and civil society actors. Laws such as the Unlawful Activities (Prevention) Act (UAPA), the National Security Act (NSA), and various state preventive detention statutes provide extensive powers to the executive to detain individuals for prolonged periods with limited judicial scrutiny. While these laws were enacted to address serious threats such as terrorism and threats to public order, their application has often raised concerns regarding the erosion of due process, presumption of innocence, and personal liberty. This article critically examines the constitutional framework of preventive detention, the functioning of anti-terror laws in India, and the implications of these laws for democratic dissent and civil liberties. The study highlights the tension between national security imperatives and fundamental rights, arguing that unchecked executive power risks criminalizing legitimate democratic dissent.